Universiti Teknologi MARA Pahang social science lecturers' involvement in research / Mohd Amli Abdullah Baharum … [et al.] - Abdullah Baharum, Mohd Amli; Azer, llyani; Mohamad, Siti Aishah; Mohd Burhan, Norhapizah; Ahmad, Badli Esham; Abd Wahid, Normilia; Abdullah, Mohd Zulkifli (2011)
This study was undertaken to identify the factors that contribute to the low involvement in research among lecturers in Universiti Teknologi MARA (UiTM) Pahang. The factors that were investigated in this study were: time, resources, knowledge and interest. The sample size of the study is 75 lecturers from a total of150 social sciences lecturers at UiTM Pahang. The data were collected through questionnaire distribution and were analyzed using descriptive statistics. The result shows that fund was the highest factor that contributed to low involvement in research, while resources was the lowest contributing factor to low involvement in research among UiTM Pahang social sciences lecturers. The findings also show that funding was the main factor for low involvement in research for Business Management, Office Management & Technology, Centre for Islamic Thought & Understanding and Accountancy lecturers. However, lecturers from the Academy of Language Studies agreed that lack of interest was the main factos for their low involvement.